Exploring reader responses to young adult literature in the Malaysian English language classroom - Mallika Vasugi V Govindarajoo; Shakina Rajendram; N. Sundari Subasini (Universitas Syiah Kuala, 2022)
This article presents the results of a study exploring the reader-responses of Malaysian young adults (YAs) to the literature texts used in Malaysian secondary schools, Dear Mr. Kilmer by Anne Schraff, Captain Nobody by Dean Pitchford, and Sing to the Dawn by Minfong Ho. The study aimed to determine the extent to which the YAs found these texts engaging and relevant, and how they identified aspects of their own young adulthood in the novels. The study employed both qualitative and quantitative data collection methods through questionnaires completed by 30 Malaysian YAs, semi-structured qualitative interviews with a sub-group of six participants, and their journal reflections. Using reader-response literary theory as the guiding framework, the data were analysed quantitatively through descriptive statistical analyses, and qualitatively through inductive thematic analysis, in order to examine the extent to which Malaysian YAs could identify with the main characters, themes, issues, or events in the novels and determine the relevance of the novels to their lives. The findings showed that the participants identified with the characters’ conflict between being true to one’s self and conforming to societal and gender expectations. The themes of standing up for one’s beliefs and right to education, combating social inequities, and family relationships were also relevant aspects that surfaced in responses towards the novels. This study provides recommendations for the selection of literary texts for the English language classroom that connect to the developmental phase of young adults and allow learners to see themselves reflected in what they read.